Impact of heavy metal pollution on the use of fishing pond land, a former site of used battery smelting - E. Riani; N.A. Butet; M. Ansori; M.R. Cordova (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Cinangka Village in Bogor Regency is a traditional used battery recycling center in West Java, Indonesia. The smelting process was operated in open space, but because of adverse impacts, it has ceased since 2010. This activity generated a large amount of solid waste, categorized as hazardous and toxic materials, thereby polluting the air, land, and water. Because an area of Cinangka Village has been converted into a fishing pond, it is necessary to investigate whether the fish that live in this pond are accumulating heavy metals, thereby threatening and harming humans as consumers. This research is important for the innovative remediation of land contaminated with used battery smelting waste.METHODS: Analysis of lead, zinc, arsenic, and iron levels in water, sediment, fish, and aquatic plants, as well as histomorphology analysis of several fish organs, was performed. The safety aspect of consuming fish originating from this location was also calculated. For the used battery recycling area, lead and iron contaminate the environment in the highest concentrations, while arsenic and zinc are always detected but in low concentrations.FINDINGS: The results showed that sediment and water around the pond, previously a burning area of used battery smelting but 12 years after cessation, are polluted by heavy metals, not only lead, zinc, arsenic, and iron. Other metals are present because lead and lead oxide plates are impure and associated with other minerals. According to the lead concentration, the soil/sediment is still categorized as hazardous and toxic material and becomes a pollutant for the ecosystem. Water hyacinth plants that live in ponds are densely cultivated and contaminated with heavy metals. They can become heavy metal phytoremediators on the land where traditional used battery burning was performed. Goldfish from this area are contaminated with high levels of heavy metals and are unfortunately unsafe for consumption because zinc is perilous. Adults are only allowed 3 grams per week, while children may not consume goldfish from this fishing pond. Contaminating heavy metals also cause various damage to fish organs, namely, edema in the kidneys, melano-macrophage centers in the spleen and liver, edema and hyperplasia in the epithelial gills, and fatty degeneration in the liver and its lysed ovary cells.CONCLUSION: Consequently, land in Cinangka Village is still categorized as hazardous, and toxic waste and should not be converted into a fishing pond because the soil is a point source of pollution that contaminates fish with high concentrations of heavy metals and damages their organs. Consuming these goldfish will harm health and thus is prohibited for children. Cleaning and remediation of the environment is necessary and must cover the entire area. Meanwhile, water hyacinth plants can be used as phytoremediators in freshwater ponds to reduce heavy metals